Short-Term Clinical Efficacy of Neoadjuvant Chemotherapy Combined With Laparoscopic Gastrectomy for Locally Advanced Siewert Type II and III Adenocarcinoma of the Esophagogastric Junction: A Retrospective, Propensity Score-Matched Study - Feng, Qing; Long, Du; Du, Ming-shan; Wang, Xiao-song; Li, Zhen-shun; Zhao, Yong-liang; Qian, Feng; Wen, Yan; Yu, Pei-wu; Shi, Yan (Frontiers in Oncology, 2021)
Background Laparoscopic gastrectomy (LG) has been increasingly used for the treatment of locally advanced Siewert type II and III adenocarcinoma of the esophagogastric junction (AEG). However, whether LG can achieve the same short-term efficacy in the treatment of patients who receive neoadjuvant chemotherapy (NACT) remains controversial. Thus, the aim of this study was to investigate the clinical outcomes of NACT combined with LG for Siewert type II and III AEG. Methods This retrospective study identified patients with locally advanced Siewert type II and III AEG diagnosed between May 2011 and October 2020 using the clinical tumor-node-metastasis (cTNM) staging system. The short-term outcomes were compared between the matched groups using a 1:3 propensity score matching (PSM) method, which was performed to reduce bias in patient selection. Results After PSM, 164 patients were selected, including 41 in the NACT group and 123 in the LG group. The baseline characteristics were similar between the two groups. Compared with the LG group, the NACT group exhibit a smaller tumor size and significantly less advanced pathological tumor classification and nodal classification stages. The time to first flatus of the NACT group was significantly shorter, but the hospital stay was significantly longer than that of the LG group. The NACT group showed similar overall (29.3% vs 25.2%, P=0.683), systemic (24.4% vs 21.1%, P=0.663), local (12.2% vs 9.8%, P=0.767), minor (19.5% vs 19.5%, P=1.000) and major (9.8% vs 5.7%, P=0.470) complications as the LG group. Subgroup analyses showed no significant differences in most stratified parameters. Operation time≥ 300 minutes was identified as an independent risk factor for overall complications. Age≥ 60 years was identified as an independent risk factor for major complications. Conclusion NACT combined with LG for AEG does not increase the risk of postoperative morbidity and mortality compared with LG.